Review paperAir pollution and non-respiratory health hazards for children - Kelishadi, Roya; Poursafa, Parinaz (Archives of Medical Science, 2010)
Air pollution is a global health issue with serious public health implications, particularly for children. Usually respiratory effects of air pollutants are considered, but this review highlights the importance of non-respiratory health hazards. In addition to short-term effects, exposure to criteria air pollutants from early life might be associated with low birth weight, increase in oxidative stress and endothelial dysfunction, which in turn might have long-term effects on chronic non-communicable diseases. In view of the emerging epidemic of chronic disease in low- and middle- income countries, the vicious cycle of rapid urbanization and increasing levels of air pollution, public health and regulatory policies for air quality protection should be integrated into the main priorities of the primary health care system and into the educational curriculum of health professionals.